Spontaneous Retrobulbar Haematoma - Mehmet Deveer; Nesat Cullu; Halil Beydilli; Hamdi Sozen; Onder Yeniceri; Selcuk Parlak (Case Reports in Radiology)
Background. Spontaneous orbital haemorrhage is a very rare condition and vision-threatening event. It may occur due to trauma, orbital surgery/injections, orbital vascular anomalies, and a variety of systemic predisposing factors. Signs of retrobulbar hemorrhage include proptosis, ophthalmoplegia, increased intraocular pressure, loss of pupillary reflexes, and optic disc or retinal pallor. Both Computed Tomography scan and Magnetic Resonance Imaging may be performed in the diagnosis. Case Report. A 31-year-old woman was referred to our hospital with a complaint of headache and blurred vision following a strong sneeze. Ophthalmological examination revealed mild Relative Afferent Pupillary Defect in left eye. Computed Tomography revealed left hyperdense retrobulbar mass and displaced optic nerve. T1 weighted hypointense, T2 weighted hyperintense and non-enhanced round shape, sharply demarcated lesion measuring 18 × 15 × 14 × mm in diameter compatible with haematoma was detected by MRI. Surgically Caldwell-Luc procedure was performed. Histological examination confirmed haematoma. Follow-up Magnetic Resonance Imaging revealed a small reduction in the size of lesion but not complete resolution. The patient’s complaint was regressed. She is now free of symptoms and is still under surveillance. To our knowledge, this is the first reported case of retrobulbar haematoma caused by sneeze.